1984
DOI: 10.1093/jn/114.9.1640
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Metabolism in Two Strains of Rats with High or Low Response of Serum Cholesterol to a Cholesterol-Rich Diet

Abstract: Transfer from a low cholesterol commercial diet to a high cholesterol diet, containing 2% (wt/wt) cholesterol and 0.5% cholate, caused an increase in serum cholesterol from about 2.5 mmol/L in two inbred rat strains to 5 mmol/L in the hyporesponsive strain and to 20 mmol/L in the hyperresponsive strain. In both strains the excess of cholesterol in the serum was exclusively located in the very low density lipoproteins. Cholesterol feeding caused a sevenfold increase in the amount of cholesterol in the liver, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
16
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 27 publications
7
16
0
Order By: Relevance
“…Nonetheless, the filling effect of alga fibers was lost when cholesterol was added to the SS diet. In agreement with Beynen et al [23], supplementary dietary cholesterol decreased the growth rate. Lower body weight gain in rabbits but not in rats fed cholesterol-enriched diets has been found [24].…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, the filling effect of alga fibers was lost when cholesterol was added to the SS diet. In agreement with Beynen et al [23], supplementary dietary cholesterol decreased the growth rate. Lower body weight gain in rabbits but not in rats fed cholesterol-enriched diets has been found [24].…”
Section: Discussionsupporting
confidence: 93%
“…The most profound effect in this respect was a marked accumulation of cholesterol and triglycĂ©rides in the liver which also has been observed in other species such as rats (Morin et al, 1962;Rönnemaa, 1976;Hulbron et al, 1982;Martins and Dhopeswharkar, 1982;Beynen et al, 1984), guinea pigs (Beck and Drevon, 1980), rabbits (Lee and Ho, 1972;Gupta et al, 1976) and mice (Lee, 1981;Reihner and Stahlberg, 1996). The extremely high concentrations of cholesterol and triglycĂ©rides in VLDL might be the consequence of a very high rate of lipid secretion from liver into blood.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies in rats (Rönnemaa, 1976;Hulbron et al, 1982;Martins and Dhopeshwarkar, 1982;Beynen et al, 1984;Huang et al, 1984;Garg et al, 1985;Stangl et al, 1993Stangl et al, , 1994a, hamsters (Ohtani et al, 1990) and rabbits (Gupta et al, 1976) demonstrated that diets rich in cholesterol markedly raise plasma cholesterol 286 K. EDER concentrations. Therefore, dietary treatment with cholesterol is a widely used model for the study of the development of atherosclerosis {e.g., Stangl et al, 1993;1994a;Loria and Padgett, 1997;Munilla and Herrera, 1997;Munday et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired cholesterol metabolism is one of the predisposing factors in the process of this disease (Beynen et al, 1984;Doucet et al, 1987;Bottger et al, 1996a). In a previous study, involving the F 2 progeny of a cross between two rat inbred strains differing in their response to dietary cholesterol, we have found several quantitative trait loci (QTLs) that are associated with cholesterol and other lipid levels in blood and liver (BonnĂ© et al, submitted).…”
mentioning
confidence: 99%